S100 Proteinase-activated Receptor 1 Signalling Contributes To Neutrophilic Inflammation And Alveolar Barrier Disruption In Streptococcus Pneumoniae Pneumonia. (10th November 2014) - José, RJ; Williams, AE; Sulikowski, MG; Brealey, DA; Brown, JS; Chambers, RC
Abstract : Introduction: Streptococcus pneumoniae is the most common cause of community-acquired pneumonia (CAP) and is associated with excessive neutrophilic inflammation. The high-affinity thrombin receptor, proteinase-activated receptor (PAR)-1, has been implicated in mediating the interplay between coagulation and inflammation. However, its role during S. pneumoniae -induced neutrophilic inflammation and the mechanisms for neutrophil recruitment in this context are poorly understood. Methods and Results: The role of neutrophilic inflammation and PAR-1 was investigated in two models of murine pneumococcal pneumonia (serotype 2 (D39) and serotype 19F (EF3030)) by using the most clinically advanced PAR-1 antagonist, SCH530348. Neutrophil depletion and chemokine neutralisation studies were also performed. Samples were analysed by immunohistochemistry, cytology, flow cytometry, ELISA and microbiological techniques. Our models were characterised by evidence of intra-alveolar coagulation, increased neutrophil recruitment to areas of bacterial infection and increased PAR-1 expression (demonstrated by quantitative image-analysis). Neutrophil depletion protected mice against barrier disruption but resulted in compromised host defence. In contrast, PAR-1 antagonist treatment significantly reduced neutrophil recruitment to the bronchoalveolar space without being detrimental to host defence. Markers of alveolar leak, coagulation activation and pro-inflammatory cytokines and chemokines (IL-1β, CXCL1, CCL2 and CCL7) were also attenuated. Neutralisation studies demonstrated that IL-1β and CCL7, but not CXCL1 and CCL2, played a key role in neutrophil recruitment to the airspaces in this model. Translational studies were performed to examine by flow cytometry the CXC and CC chemokine receptor expression on neutrophils from blood and BALF of mechanically ventilated CAP-induced ARDS patients and controls. CXCR1 and CXCR2 expression on BALF neutrophils was higher in CAP-ARDS patients compared to controls. Additionally, chemokine expression patterns on neutrophils from CAP-ARDS patients changed within different compartments, evidenced by decreased expression of CXCR1 and increased expression of CXCR2, CCR1, CCR2 and CCR3 on neutrophils from BALF compared with blood. Conclusion: These data provide preclinical proof-of-concept that recently developed PAR-1 antagonists may offer a novel therapeutic approach for controlling or preventing alveolar barrier dysfunction and excessive neutrophilic inflammation in pneumococcal pneumonia without compromising host defence. Furthermore, they highlight a role for chemokine receptor switching in CAP-ARDS with important implications for future targeting of these chemokine receptors.